Effect of basalt rock powder associated with different substrates on the initial development of aroeira seedlings (Myracrodruon urundeuva) (Research, Society and Development, 2020)
This study aimed to evaluate the initial growth of aroeira in Oxisol soil with the addition of different organic (humus and vermicompost) and organic/mineral substrates (commercial substrate) and rock powder. Seeds were collected and, after germination, transplanted to different types of substrate. The treatments assembled, with different proportions of compounds, were: T1 (50% humus + 50% Oxisol); T2 (50% commercial substrate + 50% Oxisol); T3 (50% vermicompost + 50% Oxisol); T4 (40% humus + 40% Oxisol + 20% rock powder); T5 (40% commercial substrate + 40% Oxisol + 20% rock powder); T6 (40% vermicompost + 40% Oxisol + 20% rock powder); T7 (30% humus + 30% Oxisol + 40% rock powder); T8 (30% commercial substrate + 30% Oxisol + 40% rock powder); and T9 (30% vermicompost + 30% Oxisol + 40% rock powder). Initial plant development was influenced by the treatments; 20% powder and 40% nitrogen from humus (T4) produced seedlings with the greatest root, aerial part and total weight, in addition to greatest height and collar diameter. The data obtained indicate that aroeira develops better when in argillaceous substrates, with the addition of 40% humus and 20% rock powder, indicating the adequacy of this composition for its initial growth.